Impact of Virtual Fitting Technology on Online Apparel Sales in Ghana - Mensah, Ama (International Journal of Fashion and Design, 2024)
Purpose: The aim of the study was to analyze the impact of virtual fitting technology on online apparel sales in Ghana. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: A study on the impact of virtual fitting technology on online apparel sales in Ghana found that this technology significantly increased sales conversion rates by 30% and reduced return rates by 25%. Additionally, 80% of shoppers reported an enhanced shopping experience, leading to a 35% increase in customer satisfaction and a 20% boost in repeat purchases. These findings suggest that e-commerce retailers in Ghana should adopt virtual fitting technology to improve customer confidence, reduce returns, and enhance overall sales performance. Unique Contribution to Theory, Practice and Policy: Technology acceptance model (TAM), diffusion of innovations theory & unified theory of acceptance and use of technology (UTAUT) may be used to anchor future studies on virtual fitting technology on online apparel sales in Ghana. Retailers should focus on improving the user interface and user experience of virtual fitting technologies. Policymakers should develop standards and guidelines for the use of virtual fitting technologies in online retail.